Prevalencia de tuberculosis (Mycobacterium ssp) en canales de bovinos faenados en el matadero municipal del cantón Junín - Zambrano Bermeo, Carlos Arnulfo (2023)
The present investigative study was carried out in the municipal slaughterhouse of the Junín canton, Manabí province; developed with the objective of evaluating the prevalence of bovine tuberculosis (Mycobacterium spp) in cattle carcasses slaughtered in said area. To start with its execution, lesions compatible with tuberculosis were identified by observation in the 177 bovines chosen as a population sample. The presence of Mycobacterium spp was examined through seeding in Stonebrink (ST) culture media, Ogawa Kudoh (OK) and Ziehl-Neelsen staining. Finally, the risk factors were identified: age, sex and productive aptitude; that predispose to contracting tuberculosis in the study area. From the results it was known that, of the considered sample of 177 bovines, 21 manifested lesions compatible with tuberculosis, being these the ones who had their lymph nodes sampled. The result of the laboratory tests (OK and ST cultures) showed that 9 samples presented bacterial growth; reason for which, a replanting (Ziehl-Neelsen stain) was performed to confirm or rule out its positivity. Finally, the diagnosis gave 3 positive cases for bovine tuberculosis. In conclusion, the prevalence of Mycobacterium bovis in the municipal slaughterhouse of the Junín canton is 1.69 % (3/177).